Diagnosis and definition of autism and other pervasive developmental disorders - Jackson, S.L.J.; Volkmar, F.R (Autism and Pervasive Developmental Disorders, 2019)
Keywords: dept.adm; dept.sed

Mood Disorders in High-Functioning Autism: The Importance of Alexithymia and Emotional Regulation. - Morie, Kristen P; Jackson, Scott; Zhai, Zu Wei; Potenza, Marc N; Dritschel, Barbara (Journal of Autism and Developmental Disorders, 2019)
Individuals with autism spectrum disorder (ASD) often have co-morbid anxiety and depression. Alexithymia and emotion regulation difficulties are commonly seen in individuals with ASD and in mood disorders. We hypothesized that alexithymia and emotional regulation would mediate the relationship between autistic features and anxiety/depression symptom severity. We collected data about emotional regulation, alexithymia, autistic symptoms and depression/anxiety in a sample of 64 young adults with ASD. We constructed two serial multiple mediator models, using autistic features as the independent variable and anxiety/depression symptoms as outcome variables. The serial relationship between alexithymia and emotional regulation mediated associations between autistic features and depression and anxiety, separately. The findings suggest that targeting alexithymia may benefit therapies designed to alleviate mood disorders in ASD.
43 citations (Crossref) [2023-10-31] Place: United States Morie, Kristen P. Department of Psychiatry, Yale University School of Medicine, New Haven, CT, 06510, USA. kristen.morie@yale.edu. Morie, Kristen P. Child Study Center, Yale University School of Medicine, New Haven, CT, 06510, USA. kristen.morie@yale.edu. Jackson, Scott. Department of Psychiatry, Yale University School of Medicine, New Haven, CT, 06510, USA. Scott.Jackson@yale.edu. Jackson, Scott. Child Study Center, Yale University School of Medicine, New Haven, CT, 06510, USA. Scott.Jackson@yale.edu. Jackson, Scott. Office of Assessment and Analytics, Southern Connecticut State University, 501 Crescent Street, New Haven, CT, 06515, USA. Scott.Jackson@yale.edu. Zhai, Zu Wei. Department of Psychology, Middlebury College, Middlebury, VT, 05753, USA. Potenza, Marc N. Department of Psychiatry, Yale University School of Medicine, New Haven, CT, 06510, USA. Potenza, Marc N. Child Study Center, Yale University School of Medicine, New Haven, CT, 06510, USA. Potenza, Marc N. Department of Neuroscience, Yale University School of Medicine, New Haven, CT, 06510, USA. Potenza, Marc N. Connecticut Council on Problem Gambling, Wethersfield, CT, 06109, USA. Potenza, Marc N. Connecticut Mental Health Center, New Haven, CT, 06519, USA. Dritschel, Barbara. School of Psychology & Neuroscience, University of St Andrews, St. Andrews, Fife, KY16 9JP, UK.
Keywords: *Affective Symptoms/px [Psychology]; *Autism Spectrum Disorder/px [Psychology]; *Emotions; *Mood Disorders/px [Psychology]; ASD; Adolescent; Adult; Affective Symptoms; Affective Symptoms/ep [Epidemiology]; Aged; Alexithymia; Anxiety; Anxiety Disorders; Article; Asperger Syndrome; Asperger syndrome; Autism; Autism Spectrum Disorder; Comorbidity; Depression; Emotional regulation; Emotions; Female; Humans; Male; Middle Aged; Mood Disorders; Mood disorders; Self Report; Surveys and Questionnaires; Toronto Alexithymia scale; Young Adult; adolescent; adult; aged; alexithymia; anxiety; anxiety disorder; autism; comorbidity; controlled study; depression; dept.aa; dept.adm; emotion; emotional disorder; emotionality; female; human; major clinical study; male; mental health; middle aged; mood disorder; peer-reviewed; priority journal; psychology; questionnaire; self report; young adult